HISTORICAL BACKGROUND OF THE ENGLISH-LANGUAGE CEGEPS OF QUEBEC - Edwards, Reginald (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1990)
This article presents a detailed background of the political and social changes that existed before and during the time that Quebec's CEGEP system came into existence. The objective of the article is to provide both a general history of the educational changes in Quebec in the 1960s (and the subsequent opening of the French-language CEGEPs) and the eventual opening of Dawson College, the first English-language CEGEP, in September 1969. Commentary on political, social, and economic conditions add additional insights into Quebec's present college and university education. RÉSUMÉ Cet article décrit de façon détaillée le contexte des modifications politiques et sociales survenues quant et pendant la mise en place du réseau des cégeps au Québec. L'article vise à retracer de façon générale les changements survenus dans le domaine de l'éducation au Québec au cours des années 60 (qui ont mené à la création des cégeps francophones) ainsi que la création du College Dawson, premier cégep anglophone, en september 1969. L'examen de la conjoncture politique, sociale et économique de cette période nous permet de mieux comprendre l'enseignement collégial et universitaire actuellement dispensé au Québec.